Complete mitochondrial genome of Florida pompano Trachinotus carolinus (Teleostei, Carangidae). (2nd January 2016) - Zhang, Dianchang; Wang, Long; Guo, Huayang; Ma, Zhenhua; Zhang, Nan; Lin, Junda; Jiang, Shigui
Abstract: The complete mitochondrial genome sequence of Florida pompano Trachinotus carolinus was determined by the overlapped polymerase chain reaction. The complete mitochondrial DNA sequence is 16, 544 bp in length. It consists of 13 protein-coding genes, 22 transfer RNA genes, two rRNA genes and two non-coding regions. Overall base composition of its mitochondrial genome is estimated to be 28.68% for A, 16.27% for G, 26.00% for T, 29.06% for C, respectively, with a high A+T content (54.68%). The control region contains three conserved sequence blocks, a termination-associated sequence and a TATA box. The sequence data of T. carolinus can provide useful information for the studies on population structure, molecular systematic, stock evaluation and conservation genetics. It is also helpful to develop the rational management strategies for T. carolinus resource.